Sultan Selim II’s Wedding Gifts to His Daughters Ismihan sultan, Geverhan Sultan, and Shah Sultan - Semiha Nurdan (Türkiyat Mecmuası)
Wedding, gifts are a surviving traditions that allows one to closely understand societal cullture. The tradition, is seen in almost all societies in the world throughout history,- and are prepared by the families of the engaged couple. The gifts includes all the items to be used after the marriage. And usually can take the form of beds, kitchenware, home textiles, glassware, other household items, and sometimes a piece of land. The gifts given to the bride or groom can from one society and culture to another, but giving and receiving gifts has an essentially special place in every culture. While gifts are sometimes an opportunity to establish diplomatic communications, the can appear as gifts given to a bride and groom at other times. Gifts have become a part of social communication, socialization, and cooperation. Therefore, knowing the economic, social and cultural structures is neccessary n order to conduct a study on issue of gift givings and wedding gifts. Gifts are also an indispensable part of ceremonies an celebrations. This article, first briefly mentions wedding gifts in different societies before discussing the wedding gifts Sultan Selim II gave to his daughters and sons-in-law. Acoordingly, the curriculum notebook in the Topkapı Palace Collection-contains information about the wedding gifts sultan Selim II. had prepared for Sokullu Mehmed Pasha’s wife, Ismihan Hanim Sultan, Piyale Pasha’s wife, Gevherhan Hanim Sultan, and Huseyin Pasha’s wife, Shah Sultan, these brides all being his daughters. Using the information given in curriculum and accounting books, the article will detail the types, amounts, and values of the different wedding gifts.